Supramolecular hydrogels prepared from fluorescent alkyl pyridinium acrylamide monomers and CB[8]. Issue 4 (18th December 2020) - Whitaker, Daniel J.; Huang, Zehuan; Longbottom, Brooke W.; Sala, Renata L.; Wu, Guanglu; Scherman, Oren A.
Abstract : Facile synthetic methodology unlocks alkyl pyridinium acrylamide monomers for use in the construction of cucurbit[8]uril mediated dynamic, fluorescent hydrogels. Abstract : We introduce a new facile synthetic methodology for the preparation of alkyl pyridinium-containing acrylamide monomers. Inclusion complexes of these new monomers with CB[8] facilitate supramolecular crosslinking in a series of hydrogels formed through in situ polymerisation. The resulting hydrogels not only show greatly enhanced mechanical properties over a purely acrylamide-based gel, but also by selecting fluorescent pyridine moieties, the materials are endowed with the fluorescence properties desirable for several sensing applications.